Design and Construction of Cassava Chatting Machine for Household Industry in Bulukumba District - Ratlalan, Roberth M; Odilia Valentine (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
This cassava chopping machine was made to support increased production of cassava slices ready to be fried. On a small scale, this work can be done manually with a knife or other simple cutting tool. Problems will arise if the production to be sliced or cut is available in large quantities. In order to make it easier for people to process cassava and learn about existing problems, namely, how to produce a cassava chopping machine with uniform slices using a blade disc with 4 blades. This machine uses an electric motor drive and a Speed Control speed controller. The working principle of this machine is that cassava that has been peeled is inserted into the cutting hole and then the knife disk will chop the cassava. After the cassava is chopped, the chopped results will fall into the funnel, then collected in the container that has been prepared. This cassava chopping machine can chop 157.5 kg/hour of cassava with an average thickness of 1.1 mm.